Phase change induced active metasurface devices for dynamic wavefront control. (12th March 2020) - Zhou, Shaolin; Wu, Yufei; Chen, Shanri; Liao, Shaowei; Zhang, Honglin; Xie, Changqing; Chan, Mansun
Abstract: Plasmonic metasurfaces act as appealing platforms for flexible and accurate wave regulation, but their functionalities in wavefront or spectral tuning are settled upon manufactured. So the ability to dynamically tailor the amplitude, phase or polarization is highly desirable for many scenarios of micro & nano photonics and the integrated optoelectronics. Here, one type of plasmonic metasurface devices for active wavefront control is demonstrated in the mid-infrared regime. Fundamentally, the switchable and tunable lensing is exemplified by phase change of refractive index and the generalized Snell's law as well as the Pancharatnam-Berry phase. As a proof of concept, the metal-insulator (MI) and metal-insulator-metal (MIM) architectures are employed with the phase change medium and an optimized energy conversion efficiency of cross polarization. In a wide spectral range between 2.8 μ m and 3.8 μ m, the reflective beam focuses with a cross-polarization efficiency of 80% in the amorphous state, but defocuses in the crystalline state with zero cross-polarization, i.e. the 'on' and 'off' states of the metalens. Further, both device architectures show tunable focal length from 4.4 µ m to 4.8 µ m (MI) and 3.4 µ m and 3.6 µ m (MIM) respectively upon switching between the two states. As a result, our scheme potentially paves a way to flexibly construct the active photonic devices for the reconfigurable wavefront engineering in integrated optoelectronics, i.e. beam switch, tunable steering and lensing, etc.